COLLECTIVE MEMORY IN ETHNOPOLITICAL CONFLICTS: HE CASE OF NAGORNO-KARABAKH - GARAGOZOV, Rauf (CENTRAL ASIA AND THE CAUCASUS, 2006)
There is a general agreement among those who study ethnic conflicts that collective memory may fan them, quench violence, or even prevent such conflicts,1 but it rarely becomes a subject of political studies. Strange as it may seem collective memory and its role in creating or settling ethnopolitical conflicts attract even less attention.It seems that the concept is too vague and multifaceted to serve as an analytical category. Collective memory frequently includes such notions as “bad histories” of the groups involved, historical myths, “ancient hatreds,” or is identified as the aggregate of individual memories. The absence of clear-cut differentiations is probably responsible for the researchers’ excessively cautious treatment of collective memory issues. Naturally enough the researchers want to avoid any accusations of abusing the “old ethnic hatreds” thesis. We all know that public opinion is prone to use it to explain ethnic conflicts, while experts invariably criticize this approach.Those who study ethnic conflicts often point out that it is wrong to explain conflicts by “ancient hatred” between the sides, “bad” stories about one another, past atrocities, and dreams of revenge. This is a simplified approach, since “ancient hatred” per se does not necessarily cause conflicts. This is amply confirmed by numerous examples, former Yugoslavia being one of them: it is thought that the ethnic conflicts there were politically induced by the elites. Finally, there is a widely shared opinion among experts that it is very hard to prove that it is “centuries-old ethnic hatred” that cause ethnic conflicts in the first place. They say that conflicts are fanned by many different causes, old grudges being pushed to the fore a posteriori after the conflict has been raging for some time. As a result, the idea that collective memory may play an important role in an ethnic conflict is often reduced to simply stating that it was merely one of the factors among others.Despite this I remain convinced that collective memory is an important, or even the key, factor in an ethnic or national conflict. The inability to track down and discern the specific role collective memory may play in an ethnopolitical conflict has undoubtedly infringed on our ability to prevent or resolve such conflicts. This makes it important to supply political scientists and politicians with a collective memory model to be applied to conflict analysis.